Pembentukan Karakter Kebangsaan melalui Pembelajaran Pendidikan Agama Islam di SMP Negeri 18 Mataram - Zihniatul Ulya; Ribahan Ribahan; Lubna Lubna (PALAPA, 2023)
The rapid technological advance does not rule out the possibility of eliminating the national character values in the young generation because trends, cultures and information spread very quickly, both from within and outside the country. To keep the young generation from being carried away by the negative impacts of technological advance, so the education is expected to be able to build the students’ national character through relevant learning, namely Islamic Religious Education (PAI) learning. The objectives of this research were to determine the stages, strategies, and challenges of national character building in Islamic Religious Education (PAI) learning at Public Junior High School (SMPN) 18 Mataram. The research type used was descriptive qualitative. Data collection techniques used observation, interviews, and documentation techniques. Data analysis used the data condensation, data display, and drawing conclusion or verification. The results of the research showed that (1) the stages carried out in national character building through Islamic Religious Education (PAI) learning at Public Junior High School (SMPN) 18 Mataram were inculcation, nurturing, developing, and stabilizing. Furthermore, (2) the strategies carried out were explanations, learning activities in the classroom, cultural development at school and learning activity centers, and extracurricular activities. (3) Meanwhile the challenges faced were the lack of facilities from school, association, social media, family environment, and community environment.